The Effect of Firms' Partial Retirement Policies on the Labour Market Outcomes of their Employees - Martin Huber; Michael Lechner; Conny Wunsch (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper, we assess the impact of firms introducing part-time work schemes for gradual labour market exit of elderly workers on their employees' labour market outcomes. The analysis is based on unique linked employer-employee data that combine high-quality survey and administrative data. Our results suggest that partial or gradual retirement options offered by firms are an important tool to alleviate the negative effects of low labour market attachment of elderly workers in ageing societies. When combined with financial incentives to hire unemployed or young jobseekers as replacement, they seem to be particularly beneficial, especially when labour market conditions are difficult. Under such circumstances, they can even have positive spill-over effects on younger workers. Firms should thus be encouraged to offer such schemes.
Keywords: J14; J26; C21; 330; part-time work; elderly employees; treatment effects; matching